2005
DOI: 10.1007/s00213-005-2214-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging studies of opioid receptor-mediated modulation of noxious-evoked BOLD contrast in rats

Abstract: Our data demonstrate that morphine modulates noxious-evoked changes in signal intensity in discrete brain regions. fMRI studies in rats are able to identify specific brain regions involved in the pharmacological modification of physiologically evoked changes in regional brain activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 52 publications
2
41
1
Order By: Relevance
“…Our results for morphine appear to contradict those obtained in a recent study using BOLD signal (Shah et al, 2005), but it is more difficult to relate our results to patterns of heroininduced brain stimulation. IV heroin is metabolized to both morphine and 6-acetylmorphine, and the latter acts more like a high-efficacy MOR agonist of the fentanyl class than like morphine (Selley et al, 2001).…”
Section: Spatial Distribution Of Fcbv Changescontrasting
confidence: 57%
See 2 more Smart Citations
“…Our results for morphine appear to contradict those obtained in a recent study using BOLD signal (Shah et al, 2005), but it is more difficult to relate our results to patterns of heroininduced brain stimulation. IV heroin is metabolized to both morphine and 6-acetylmorphine, and the latter acts more like a high-efficacy MOR agonist of the fentanyl class than like morphine (Selley et al, 2001).…”
Section: Spatial Distribution Of Fcbv Changescontrasting
confidence: 57%
“…Functional MRI in rats using restricted brain coverage has produced disparate results for this class of drugs. Morphine has been reported to induce positive changes in BOLD signal (Shah et al, 2005), in apparent contradiction with decreased glucose metabolism observed in another study (Cohen et al, 1991). Heroin produced predominantly negative changes in BOLD signal, with some positively responding voxels in cortex (Xi et al, 2002).…”
Section: Introductionmentioning
confidence: 43%
See 1 more Smart Citation
“…One parameter that may affect the magnitude of BOLD responses is abrupt changes of blood pressure (Kalisch et al, 2001;Tuor et al, 2002). Gradual changes that remain within the range of effective cerebral autoregulation are less likely to be associated with BOLD signal alterations (Zaharchuk et al, 1999;Shah et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…fMRI studies in animals are also being used to examine effects of analgesics. For example, treatment of the paw with formalin produced bilateral increases in cerebral blood flow in somatosensory cortex, cingulate, and the periaqueductal gray area in rats, and pretreatment with morphine attenuated these formalin-induced fMRI effects (Shah et al, 2005). Morphine also blocked pain-associated fMRI responses to electrical stimulation and injection of capsaicin (Tuor et al, 2000;Malisza and Docherty, 2001).…”
Section: Downloaded Frommentioning
confidence: 99%